Comparison of purification methods to purify recombinant bromelain from Escherichia coli BL21-A1 = Perbandingan kaedah penulenan rekombinan bromelain daripada Escherichia coli BL21-A1 - Mohd Arshad, Zatul Iffah; Amid, Azura; Yusof, Faridah; Sulaiman, Siti Zubaidah; Abdul Mudalip, Siti Kholijah; Che Man, Rohaida; Md Shaarani, Shalyda (Faculty of Science and Technology, Universiti Kebangsaan Malaysia, 2017)
Recombinant bromelain is a cysteine protease that can be exploited for its protease activity in food and pharmaceutical applications. The aim of this study was to compare different purification methods aqueous two-phase system (ATPS), ammonium sulphate precipitation, ion exchange, affinity, and gel filtration chromatography) for the recombinant bromelain purification from Escherichia coli BL21-A1. From the SDS-PAGE analysis, all methods produced band with molecular weight between 50 to 55 kDa. Among the methods used, the ATPS purification consisting of 13% (w/w) of PEG6000 and 11% (w/w) potassium phosphate at pH 7.0 was chosen as the best purification method. The method produced 16.39 ± 0.03 % of yield, purification fold of 5.35 ± 0.11, and specific activity of 3.47 ± 0.11 unit/mg of recombinant bromelain. This proposed study can be used as a platform for large-scale downstream processing of recombinant bromelain in industry.